2014
DOI: 10.1002/mnfr.201400317
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identifies cytoskeleton‐interacting proteins as major downstream targets of altered folate status in the aorta of adult rat

Abstract: Our proteomic study supports that expression of proteins essential to vascular structure and, presumably, function is modulated by high intake as well as deprivation of FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…However 40% of samples are discarded as outliers and the simultaneous examination of mthfr +/and dietary folate deficiency does not allow proteomic adaptations to be attributed to either in isolation [121]. In a 2DGE-MS-based study of adult rats, aortic calmodulin (CALM1, calcium signaling) protein abundances are positively correlated with folate dose while abundances of triose phosphate isomerase (TPI1, glycolysis), transgelin (TAGLN, cytoskeleton), and glutathione s-transferase alpha 3 (GSTA3, reductive detoxification) respond inversely [122]. In an 2DGE-MS-based study of rat livers, PRDX6 and GPX1 are reported to be elevated while cofilin (CFL1) is reported to be depleted under folate deficiency [123].…”
Section: Vitamin Bmentioning
confidence: 99%
“…However 40% of samples are discarded as outliers and the simultaneous examination of mthfr +/and dietary folate deficiency does not allow proteomic adaptations to be attributed to either in isolation [121]. In a 2DGE-MS-based study of adult rats, aortic calmodulin (CALM1, calcium signaling) protein abundances are positively correlated with folate dose while abundances of triose phosphate isomerase (TPI1, glycolysis), transgelin (TAGLN, cytoskeleton), and glutathione s-transferase alpha 3 (GSTA3, reductive detoxification) respond inversely [122]. In an 2DGE-MS-based study of rat livers, PRDX6 and GPX1 are reported to be elevated while cofilin (CFL1) is reported to be depleted under folate deficiency [123].…”
Section: Vitamin Bmentioning
confidence: 99%